Armenia Economic Report, Spring 2014 : Looking for More Dynamism - World Bank (World Bank, Washington, DC, 2017)
This regular economic report records the economic activities of Armenia for the year 2013-2014. A decline in construction contributed to a significant weakening of economic growth in Armenia in 2013. The decline of the construction sector offset a dynamic expansion of industry, agriculture and services. The volume of merchandise exports rose by 7.2 percent, and net remittances exceeded 1.5 billion US dollars, a 15-percent increase over 2012. For a third year in a row, the execution of public capital spending was lower than budgeted. Tax revenues were in line with the budget because of improved tax administration, policy measures that expanded the tax base, and a one-off license fee paid by the fourth mobile phone operator. Armenia needs to further improve the business environment and competitiveness, and facilitate FDI and exports to create well-paying jobs. Some employees objected to the introduction of the new, funded pension system, and opposition parties appealed against some legal provisions in court. The government’s medium-term reform agenda, supported by the ongoing Development Policy Operation supported by the World Bank reflects the priorities. It includes critical reforms to the business climate and public administration aimed at strengthening competitiveness and increasing public sector efficiency. These reforms are expected to create jobs by reducing the costs of doing business for firms, expanding access to credit to Small and medium enterprises (SMEs), and increasing opportunities for employment and job creation through increased trade and connectivity. The public administration reforms, which aim to strengthen resource management and policy formulation, will also facilitate more inclusive access to services as a result of more efficient use of resources and a sounder policy formulation framework. The government plans to call a Consultative Group Meeting to seek donors’ support for upgrading the country’s competitiveness and addressing the country’s job creation agenda.